Development of a passive VHF radar system using software‐defined radio for equatorial plasma instability studies. Issue 4 (9th August 2013) - Tuysuz, B.; Urbina, J.; Lind, F. D.
<x xml:space="preserve">Abstract</x> [1] In this paper, a bistatic passive radar receiver system named "Coherent‐scatter Atmospheric Passive Radar Imager (CAPRI)" is described. It is primarily designed to study the dynamics of the upper atmosphere by utilizing "transmitters of opportunity" as the RF target illuminators. CAPRI is constructed using the open source software‐defined radio toolkit, GNU Radio, to meet the signal processing requirements in combination with the open source hardware, Universal Software Radio Peripheral 2, for data acquisition. The resultant system is highly flexible, and we present the details of the design as well as a performance analysis. CAPRI will be deployed in Peru, near the magnetic equator, for long‐term operations in the area. FM stations near Lima, Peru, will be utilized with the targets of interest being the equatorial electrojet and the spread F. The results will then be compared to the Jicamarca Unattended Long‐term investigations of the Ionosphere and Atmosphere (JULIA) radar data, and CAPRI will be used to improve the simultaneous time and spatial coverage in the region in a more cost‐effective manner.